Pharmacogenomics In Pharmacy Practice: Current Perspectives - Elewa H; Awaisu A (Dove Medical Press, 2019)
Hazem Elewa, Ahmed Awaisu College of Pharmacy, Qatar University Health, Qatar University, Doha, QatarCorrespondence: Hazem ElewaCollege of Pharmacy, Qatar University Health, Qatar University, P.O. Box 2713, Doha, QatarEmail elewahazem@gmail.comAbstract: Pharmacogenomics (i.e., the application of genetic information in predicting an individual’s response to drug therapy) plays an increasingly important role in drug development and decision-making regarding precision medicine. This has been shown to reduce the risk of adverse events and improve patient health-care outcomes through targeted therapies and dosing. As the field of pharmacogenomics rapidly evolves, the role of pharmacists in the education, implementation, and research applications of pharmacogenomics is becoming increasingly recognized. This paper aims to provide an overview and current perspectives of pharmacogenomics in contemporary clinical pharmacy practice and to discuss the future directions on advancing pharmacogenomics education, application, and research in pharmacy practice.Keywords: pharmacogenomics, pharmacy practice, precision medicine, pharmacist role